Brick solo cement with vegetable fiber addition: an alternative in civil construction (Research, Society and Development, 2018)
With the scarcity of materials sustainaible in civil construction, we think in the alternative of use of new experiments,to increase of resistance and durability  of the brick,  such as fiber  vegetable what beyond to be a product sustainable  and from below can also add great results to their composites. This one job has with the objective, to make bricks solo  cement with addition  of the fiber vegetable  and analyze its main characteristics physical mechanics . The materials used were: ground, cement water, their essay were made at University  Antônio Carlos, the first we got the characterization of ground, on Monday stages were made the bricks with one press manual and for last were made test gives resistance the compression and absorption  in  water we brick.